AB0612 Efficacy of Subcutaneous Immunoglobulins (SCIG) in Refractory Inflammatory Myopathies. (10th June 2014) - Gambini, S.; Gelardi, C.; Moretti, R.; Pedini, V.; Gabrielli, A.; Danieli, M.G.
Abstract : Objectives: To evaluate the efficacy of subcutaneous of immunoglobulins (SCIg) in 13 patients with refractory polymyositis (PM) and dermatomyositis (DM). Methods: We described 13 patients (10 female and 3 male) with PM (5) and DM (8), diagnosed according to the Bohan and Peter's criteria, with a mean age of 50 years and a mean disease duration of 72 months. Prior SCIg treatment, all patients received high dose oral glucocorticoids associated to several immunosuppressive agents with no sustained improvement. Mean follow-up period was 20 months. We used a standardized protocol of infusion consisting on the administration of a weekly dose of 0.2 g/kg/week of SCIg, by the means of a programmable pump, changing sites of administration every week. After a three weeks of in hospital training period, patients were switched to home management. Results: Treatments response was evaluated using clinical and laboratory data. We documented a significant improvement on serum CK levels, MRC score and Rankin modified score. Prednisone daily dose was reduced in all patient. Neither systemic adverse events nor relapses were reported. Conclusions: Our data showed the effectiveness and the good tolerance of SCIg as a valid treatment option in active and severe form of myopathies, also as steroid-sparing agents. However, a longer follow-up period is necessary to evaluate their efficacy as an alternative to intravenous route of administration (IVIg treatment). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3610